Diversidade e desenvolvimento de girinos (Amphibia, Anura) em corpos d’água associados a fragmentos de mata no nordeste do Brasil - OLIVEIRA, Daniel Brito de (2010)
Urbanization brings many consequences such as fragmentation and degradation of the remaining forest fragments. Degradation in these fragments can negatively affect the forest species, but favor their use by open area species. Thus we aimed to investigate if tadpoles of open area species are developing, together with those of forest species, in water bodies located in forest fragments in Sao Luis Island, MA, Brazil. For this we collected tadpoles in 32 pools with varied characteristics divided into three different types of environment (open area, outer edge of the forest, and forest interior), during the years 2008 and 2009. We recorded 20 species in five families (Bufonidae, Hylidae, Leptodactylidae, Leiuperidae, Microhylidae). The environmental variables accounted for much of the variation in the abundance of tadpoles, and the percentage of vegetation in the pool, the vegetation height in the forest edge, the distance to the forest, and the depth of the pool showed significative effects. Tadpoles of open area species occured in water bodies located in the forest interior. The increased presence of generalist species, and the reproductive success of open area species in the forests indicate that these areas are impacted.